The Contribution of Agro forestry System to Tree Biodiversity Conservation and Rural Livelihood: The Case of Lay Armachiho District, Gondar, Ethiopia. (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of this study was to assess the contribution of agro forestry system to tree biodiversity conservation and rural livelihood improvement, specifically, on-farm tree species diversity, evenness, richness indices, to examine the role of agro forestry system to biodiversity conservation and analyzing the contribution of agro forestry system to rural livelihood improvement. A total of 112 households were selected for the study based on simple random sampling. The collected primary data were analyzed by descriptive and inferential statistics by using Statistical Package for Social Science (SPSS) and MS Excel.Shannon and Simpson’s diversity index, evenness and species richness were used to analyze on-farm tree species diversity, evenness and richness. Sorensen coefficient of similarity was used to analyze on-farm tree similarity. Species richness and evenness were very high in study area, which is higher in Weyna dega parkland than home garden and trees on pasture land. Similarly, home garden is lower than trees on pasture lands. Agro forestry systems showed the direct relationship of biodiversity conservation and planted/maintained of multipurpose tree species on farmland especially in parkland with the contribution of diverse benefits of the farmers to improve their socioeconomic condition. There were 77 tree/shrub species with their respective number of 36 families found in the study area. More than 18% of annual average of household income comes from agro forestry practices. Some of the agro forestry tangible product that benefits the households was fodder, fruit, fuel wood, and cash crops.